Systematics of Juncaceae - Jones, Eleanor (Trinity College (Dublin, Ireland). Department of Botany, 2008)
The systematics of Juncaceae is investigated using morphological and molecular data. A study of the anatomy of Juncaceae is presented as anatomical descriptions of the leaves, including observations of previously undescribed taxonomically informative characters, particularly in the leaf sheaths. The DNA regions ITS, rps16, trnL intron and trnL-F intergenic spacer are sequenced. Molecular, morphological and combined cladistic analyses are carried out, resulting in a phylogenetic hypothesis of Juncaceae. Juncaceae is shown to be a sister group to Cyperaceae. Within Juncaceae, Luzula is shown to be monophyletic, but Juncus is paraphyletic with respect to Distichia, Marsippospermum , Oxychloe, Patosia and Rostkovia. Within Juncus, however, two well-supported clades are identified (Clades A and B), and a third clade (C) contains the remaining species of Juncus and all other genera except for Luzula.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin